Pelatihan dan Pendampingan: Anak Muda Melek Social Media Marketing - Naufal Sinatria; Fauzan Fuadi; Muhammad Lathief Syaifussalam; Nur Aminudin; Dwi Feriyanto; Agus Wantoro; Andi Mulyono (Dharma: Jurnal Pengabdian Masyarakat, 2026)
The aim of this marketing content creation training and mentoring is to increase students' understanding, creativity, and confidence in creating simple content, as a generation growing up in the digital era. The methods used include material delivery, interactive discussions, and direct practice. The results showed high student enthusiasm throughout the process, indicating that the learning approach aligned with their characteristics and needs. In addition to acquiring basic content creation skills, students also demonstrated positive developments in their expressive and collaborative abilities. These results demonstrate that hands-on learning is highly effective in developing students' digital competencies.